Characterization of COVID-19 Hospitalized Patients in Three United States Electronic Health Record Databases - Patrick Saunders-Hastings; Cindy Ke Zhou; Shayan Hobbi; Eva Boyd; Patricia Lloyd; Nader Alawar; Timothy Burrell; Jeff Beers; Tainya C. Clarke; Aaron Z. Hettinger; Hui-Lee Wong; Azadeh Shoaibi (Pathogens, 2023)
COVID-19 infections have contributed to substantial increases in hospitalizations. This study describes demographics, baseline clinical characteristics and treatments, and clinical outcomes among U.S. patients admitted to hospitals with COVID-19 during the prevaccine phase of the pandemic. A total of 20,446 hospitalized patients with a positive COVID-19 nucleic acid amplification test were identified from three large electronic health record databases during 5 February–30 November 2020 (Academic Health System: n = 4504; Explorys; n = 7492; OneFlorida: n = 8450). Over 90% of patients were ≥30 years of age, with an even distribution between sexes. At least one comorbidity was recorded in 84.6–96.1% of patients; cardiovascular and respiratory conditions (28.8–50.3%) and diabetes (25.6–44.4%) were most common. Anticoagulants were the most frequently reported medications on or up to 28 days after admission (44.5–81.7%). Remdesivir was administered to 14.1–24.6% of patients and increased over time. Patients exhibited higher COVID-19 severity 14 days following admission than the 14 days prior to and on admission. The length of in-patient hospital stay ranged from a median of 4 to 6 days, and over 85% of patients were discharged alive. These results promote understanding of the clinical characteristics and hospital-resource utilization associated with hospitalized COVID-19 over time.